PRINSIP-PRINSIP EKONOMI ISLAM DALAM SIMBOL WARAK NGENDHOG PERSPEKTIF HERMENEUTIKA DILTHEY - Faizah, Fita Nurotul (Academic Journal of Islamic Principles and Philosophy, 2025)
This research aims to explore the meaning of the warak ngendhog symbol through Dilthey's hermeneutics and its relevance to Islamic economic principles. The method chosen in this research is qualitative with field studies. Data were collected through interviews, non-participatory observation and documentation, then analyzed using Wilhelm Dilthey's hermeneutics through three aspects: experience (erlebniz), expression (ausdruck), and deep understanding (verstehen). The results are then connected descriptively with the principles of Islamic economics. The research findings are that the Warak Ngendhog symbol contains religious, social, aesthetic and political values. According to Dilthey's hermeneutics, every series of dugderan including the Warak Ngendhog symbol provides an experience of the historicity of the tradition, expression, and understanding of the culture. Furthermore, in the context of Islamic economic principles, Warak Ngendhog reflects the value of tawhid through the unity of cultural diversity, the principle of justice ('adl) in socio-economic activities, the principle of nubuwwah (sidiq, amanah, tabligh, and fathanah), describing the role of khilafah in the management of a just economy and ma'ad as a spiritual awareness of the blessing and accountability of charity. This tradition serves as a cultural preservation and Islamic economic education media that integrates social, religious, and economic aspects in the lives of the people of Semarang city.